A case of nodular fasciitis involving the tongue. Issue 3 (May 2015) - Hino, Shunsuke; Masuda, Issei; Fukai, Shunichi; Kaneko, Takahiro; Horie, Norio; Shimoyama, Tetsuo
Abstract Nodular fasciitis (NF) is defined as a benign and reactive fibroblastic growth extending from the superficial fascia into subcutaneous tissue or muscle. NF shows rapid growth, and pathological diagnosis can be difficult, so this entity is sometimes misdiagnosed as malignant tumor. NF can arise anywhere in the body, but occurrence in the oral region is rare and only four cases of NF involving the tongue have been reported previously. We describe herein a new case of NF in the tongue. The patient was a 37-year-old man who presented with a painless mass in the tongue that had grown rapidly over 7 days. After radiographic examination and biopsy, the mass was excised. Immunohistochemically, the specimen showed positive results for desmin and alpha smooth muscle actin, dispersive positive staining for CD-34, and weak positive results for CD-68. No signs of recurrence have been seen during the 24 months of follow-up.